Development of Recommendations for Improving the Interaction Efficiency Between the Components of the «Sender-Carrier-Recipient» System - Zelenko, J. V; Kalymbet, M. V (Science and Transport Progress, 2022)
Purpose. The study is aimed at developing recommendations for improving the efficiency of the relevant units of the «sender-carrier-recipient» system for correcting their work on railway safety management during the transportation of dangerous goods and/or during an emergency situation. Methodology. On the basis of graphic, analytical tools and with the help of the probability theory, the assessment of the emergency situation occurrence was analyzed. Findings. On the basis of the combined Ishikawa diagram of the key event tree and the risk map of the key event, an analysis of the risk assessment of the emergency situation was carried out. Possible causes and factors of the occurrence of emergency situations during the transportation of dangerous goods by railway transport (hit by a missile, ice, speeding, obstacles on the railway track) were identified. Recommendations have been developed to reduce the risks of an emergency situation (cooperation between Ukrzaliznytsia PJSC and relevant centers that conduct special training on the transportation of dangerous goods, effective interaction of all participants in the «sender-carrier-recipient» system, as well as perfect control over compliance with the rules. Development of proposals for improving the procedure of interaction between the relevant units of the «sender-carrier-recipient» system, which can be involved in liquidation measures (Using universal sorption cloth (USC) for localization of spills of dangerous goods, using wagons of models 19- 795 and 19–795–01 for transportation of USC, regeneration and reuse of USC.). Originality. Specific recommendations for minimizing the negative consequences of accidents based on a systematic analysis and assessment of the risks of an emergency situation during the transportation of dangerous goods by railway transport were developed. Practical value. In the field of security the application of these recommendations will contribute to the reduction of risks in railway transport from the point of view of preventing the occurrence of a situation that would threaten the ecological state of the environment and human life, especially in the conditions of a state of war taking place on the territory of our country, as well as the renewal of material and technical means of liquidation of accident consequences.